ANALISA PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP DISIPLIN KERJA YANG BERDAMPAK PADA PENINGKATAN KINERJA DOSEN POLITEKNIK SWADHARMA - Sugiyono Sugiyono (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2020)
Leadership, motivation, work discipline are very important factors in efforts to develop human resources in improving lecturer performance. This study is to determine the effect of leadership, motivation and work discipline on lecturer performance. This quantitative research is using multiple linear analysis. The sample of this study were 57 lecturers of Swadharma Polytechnic. The results of calculations with multiple liner analysis show that (1) the t test: the leadership variable test (1.876), the motivation variable (1.294), and the work discipline variable (3.605) have a t value greater than 0.05, namely 1.98. This means that these variables have a positive effect on lecturer performance. (2) f test: 8,382 with a significance level of 0,000. This significance value is still below the specified significance value of 0.05 and is positive, so it can be concluded that leadership, motivation and work discipline together have a significant influence on lecturer performance. (3) R2 test: equal to 0.283, the coefficient value is between 0 and 1. This shows that the ability of the leadership, motivation and work discipline variables to explain their effect on the performance variable is 2.83% while the remaining 7.17% is the influence of the independent variables. others who were not examined in this study